If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + 3(-4n + 6) = -2(-7n + -5) + -3 Reorder the terms: -1 + 3(6 + -4n) = -2(-7n + -5) + -3 -1 + (6 * 3 + -4n * 3) = -2(-7n + -5) + -3 -1 + (18 + -12n) = -2(-7n + -5) + -3 Combine like terms: -1 + 18 = 17 17 + -12n = -2(-7n + -5) + -3 Reorder the terms: 17 + -12n = -2(-5 + -7n) + -3 17 + -12n = (-5 * -2 + -7n * -2) + -3 17 + -12n = (10 + 14n) + -3 Reorder the terms: 17 + -12n = 10 + -3 + 14n Combine like terms: 10 + -3 = 7 17 + -12n = 7 + 14n Solving 17 + -12n = 7 + 14n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-14n' to each side of the equation. 17 + -12n + -14n = 7 + 14n + -14n Combine like terms: -12n + -14n = -26n 17 + -26n = 7 + 14n + -14n Combine like terms: 14n + -14n = 0 17 + -26n = 7 + 0 17 + -26n = 7 Add '-17' to each side of the equation. 17 + -17 + -26n = 7 + -17 Combine like terms: 17 + -17 = 0 0 + -26n = 7 + -17 -26n = 7 + -17 Combine like terms: 7 + -17 = -10 -26n = -10 Divide each side by '-26'. n = 0.3846153846 Simplifying n = 0.3846153846
| 9D-5-5D=23 | | 4abcde*20a^2b^3= | | -12+-3=-36 | | 13n-13=(-12) | | 4+2(x-3)=2[4-6(x+2)] | | 15y=7y+16 | | 12x^2+5x-32=0 | | 2m-4+2m=80 | | 48-31y= | | 7C-4C+3=54 | | -3z+26-2z=6 | | -3(5t-5)+8t=7t-4 | | 400-10=306.25-3x | | 2x-7(4x+17)=-379 | | (5a)(6b)(2c)= | | y=0.3+5.2 | | 2x^2+x-.25=0 | | 4B+6B-4=86 | | 4r=1+-2r | | 9x+7p=142506 | | 0=10x^3-11x^2-47x+30 | | 8x-10=7x-3x | | 3(2x+12)+5x-22= | | 4[-4(4x+3)+4(5x-4)]= | | 25xy=300 | | (4x-8)(9ab+12)= | | 0.2=x^3-4x+9 | | 25x-27=16x-6x | | X=-4+-3y | | 3F+8=80-6F | | -5(4t-5)+6t=8t-4 | | 4E-15=20-3E |